Rezension zu: Demmrich, Sarah / Riegel, Ulrich (Hg.): Western and Eastern Perspectives on Religion and Religiosity - Aslan, Ednan (Österreichisches Religionspädagogisches Forum, 2022)
Rezension DEMRICH, Sarah / RIEGEL, Ulrich (Hg.): Western and Eastern Perspectives on Religion and Religiosity, Münster / New York: Waxmann 2021 (= Research on Religious and Spiritual Education 14).